A Survey on Resource Allocation Techniques in Cloud Computing - P, Lijin P; S. SivaSathya, Dr; S .Guruprakash, K (International Journal of Engineering and Technology, 2018)
Cloud computing has become the most popular technology that provides a fast and cost-effective way to configure and allocate resources to the users on demand. The user gets to pay for every service being used from the cloud. It is vey important to consider the user requirements while allocating resources to the user. Virtualization technology is the core of cloud computing. Virtual machines are created from a set of physical machines and these VMs are allocated to the user based on their requirements. The Cloud user has to provide accurate parameters during configuration in order to avail the resources effectively. This paper presents a survey on different resource allocation techniques for cloud.Â Â